Paratransit Ergonomics - Kuntohadi, Hendro; Pahala, Yosi; Gunawan, Aang (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2014)
In order to improve effectiveness, ergonomics is needed in every part of our activities including in designing the paratransit. Through library research, mini lab-testing, and field study, we could find out how ergonomics our paratransit is, in this case paratransit route Pusat Grosir Cililitan (PGC) Mekar Sari. Based on the study, it is revealed that the ergonomics value which should be applied cannot be achieved due to overloaded passengers of the transportation that caused inconvenience.